Practical guide for the application of the Genebank Standards for Plant Genetic Resources for Food and Agriculture: Conservation through cryopreservation - Furman, Bonnie; Volk, Gayle; Ballesteros, Daniel; Bettoni, Jean Carlos; Guarino, Luigi; Gupta, Sandya; Hassan, Niveen; Hay, Fiona R.; Krishnan, Sarada; Lusty, Charlotte; Marino, Mario; Noorani, Arshiya; et al. (Commission on Genetic Resources for Food and Agriculture, 2025)
The Food and Agriculture Organization of the United Nations (FAO) has developed the Practical guide for the application of the Genebank Standards for Plant Genetic Resources for Food and Agriculture: Conservation through cryopreservation to be used as a companion volume to the Genebank Standards for Plant Genetic Resources for Food and Agriculture. The action steps of the genebank workflow are presented in a sequential manner and provide guidance on the complex steps and decisions required when utilizing cryopreservation in a genebank. The accompanying summary charts for the respective action steps underscore the intended use of this practical guide as a handbook for routine genebank operations for cryopreservation. While this practical guide is particularly useful for genebank technicians for their day-to-day activities, it may also be used as a basis for the development of standard operating procedures and quality management systems. Genebank managers will also find it useful for conducting training exercises.